1989
DOI: 10.1029/jd094id13p16303
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric infrared continuum absorptions observed by the ATMOS instrument

Abstract: A quantitative analysis of continuum absorptions in the lower stratosphere is reported based on infrared solar absorption spectra recorded in the occultation mode at 0.01 cm−1 resolution. The spectra were obtained during seven sunrises near 48°S latitude and 12 sunsets near 28°N latitude with the atmospheric trace molecule spectroscopy (ATMOS) Fourier transform spectrometer operating April 29 to May 1, 1985, on board the shuttle/Spacelab 3 platform. Continuous absorption produced primarily by the collision‐ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…However, we carried out our computations using version 2.4 of the CKD model (hence after referred to as CKD v2.4) that became available at the time the regression coefficients were about to be generated. The pressure-broadened band of N 2 at 2350 cm −1 (Menoux at al., 1993) and that of O 2 at 1550 cm −1 (Timofeyev and Tonkov, 1978;Rinsland et al, 1989) is included as broadband continuum contribution to the absorption and heavy molecules can be modeled using high-resolution cross-sectional data. In our computations, CO 2 Q-branch line mixing has been fully accounted for using first order line-mixing coefficients from Strow et al (1994).…”
Section: Genln2 V4mentioning
confidence: 99%
“…However, we carried out our computations using version 2.4 of the CKD model (hence after referred to as CKD v2.4) that became available at the time the regression coefficients were about to be generated. The pressure-broadened band of N 2 at 2350 cm −1 (Menoux at al., 1993) and that of O 2 at 1550 cm −1 (Timofeyev and Tonkov, 1978;Rinsland et al, 1989) is included as broadband continuum contribution to the absorption and heavy molecules can be modeled using high-resolution cross-sectional data. In our computations, CO 2 Q-branch line mixing has been fully accounted for using first order line-mixing coefficients from Strow et al (1994).…”
Section: Genln2 V4mentioning
confidence: 99%
“…Rinsland et al [1981] confirmed these observations by analysis of balloon-borne limb solar occultation spectra. A further detailed analysis of the mid-infrared continuum signals of O 2 and N 2 has been performed on basis of space-borne observations by Rinsland et al [1989].…”
Section: Introductionmentioning
confidence: 99%
“…Continuum absorption in this region is produced by the superposition of absorption from collision‐induced fundamental vibration‐rotation band of N 2 and distant wings of lines from the strong CO 2 ν 3 fundamental band at 2349 cm −1 . The continuum has been studied using ground‐based, aircraft‐borne, and balloon‐borne spectra (see the references cited by Rinsland et al [1989], section 5, for early measurements). More recent experimental and theoretical studies of the 4.3 μm N 2 continuum include the papers by Lafferty et al [1996] and Moreau et al [2001].…”
Section: Introductionmentioning
confidence: 99%